Successful Treatment of Disseminated Subcutaneous Panniculitis-Like T-Cell Lymphoma with Single Agent Oral Cyclosporine as a First Line Therapy - Nida Iqbal; Vinod Raina (Case Reports in Dermatological Medicine)
Subcutaneous panniculitis-like T-cell lymphoma (SPTL) is a rare cutaneous neoplasm of mature cytotoxic T-cells. Currently there are no standardized therapies for SPTL; however good responses have been seen with chemotherapy regimens generally employed for B-cell lymphomas. Cyclosporine, an immunosuppressant, has shown good responses in relapsed/refractory SPTL; however its use in first line setting is not well established. We, herein, describe a 22-year-old girl with disseminated SPTL who attained complete clinical remission with single agent oral cyclosporine used as a first line therapy.